Russian Initiatives in Internet Governance - S. S. Shirin (Vestnik MGIMO-Universiteta, 2014)
The article is devoted to the research of Russian initiatives concerning its participation in international system of Internet governance. In the research, conceptual and theoretic basis for participation of state governments in Internet governance is given, academic discourse of this issue is assessed, the review of main Russian initiatives made from 2005 (since the second stage of the World Summit on Information Society) till the present day is carried out. The conclusion is made that the most successful Internet governance initiative of Russia is the implementation of cyrillic top level domains. Much less successful are Russian attempts to reconstruct existing organizational structure of Internet governance. Russian policy is assessed as a policy of preferring loud statements and PR rather than real influence on development of Internet technologies. Russia consideres Internet as political resource and tries to increase its influence on decision making process on a political, not operational level of Internet governance. The author states that federal government of the United States of America has fully lost the control on the domain name systems. These functions are going to be given to the private sector, while ICANN, which was established according to the Memorandum of Understanding/Joint Project Agreement with U.S. Department of Commerce, is becoming a truly independent international organization. Considering this, the author comes to the conclusion that political transformations for the sake of Russia are already made. He also forecast that next initiatives of Russia will be directed to the segmentation of the Internet.